Idiopathic Interstitial Pneumonia as a Possible Cause of Antineutrophil Cytoplasmic Antibody-Associated Vasculitis: A Case Report - Hiroshi OIWA; Katsuhiro OOI; Tetsu OYAMA; Eiji SUGYAMA (Archives of Rheumatology, 2018)
There are conflicting data to date on the causal relationship between idiopathic interstitial pneumonia and antineutrophil cytoplasmic antibody (ANCA): (1) myeloperoxidase-ANCA may play a pathogenetic role in pulmonary fibrosis, or (2) pulmonary fibrosis may induce production of the antibody. In this article, we describe a case of an elderly female patient with microscopic polyangiitis that developed after positive conversion of myeloperoxidase-ANCA during the course of idiopathic interstitial pneumonia. Our experience as well as similar case reports may suggest that idiopathic interstitial pneumonia may induce production of ANCAs and even ANCA-associated vasculitis.